Gammaropsis elvirae sp. nov., a widely distributed amphipod (Amphipoda: Photidae) in the Yucatan Shelf, with ecological comments and a key for the genus in tropical America - Paz-Ríos, Carlos E.; Pech, Daniel (Zootaxa, 2019)
Gammaropsis elvirae sp. nov. is described and illustrated here, as a new species of the family Photidae Boeck, 1871, occurring on sites widely distributed in the soft-sediment habitats from the Yucatan shelf, southern Gulf of Mexico. This new species differs from all other congeners by a unique set of characteristics: lateral cephalic lobes rounded; outer lobes of lower lip with one cone on each lobe; gnathopod 1 propodus longer than carpus; gnathopod 2 propodus enlarged with small convoluted processes on posterior margin and palmar angle undefined; gnathopod 2 dactylus short, less than one half in length of propodus; dense setation on basis, carpus, and propodus of gnathopod 2; epimeral plates 1–3 rounded; inner ramus of uropods 1–3 longer than outer ramus; and telson emarginated. Ecological comments on spatial distribution and associated environmental variables are included, as well an identification key to the genus in tropical America.